Personal value system as related to anti-minority attitude in Muslim students of Rajshahi University, Bangladesh (Journal of Life and Earth Science, 2011)
Relationships between personal values and anti-minority attitude in a group of 100 Muslim students of Rajshahi University were estimated using adapted Bengali versions of Allport-Vernon-Lindzey study of values and Levinson-Sanford Anti-Semitism scale. The relationships between anti-minority attitude and each of the Spranger’s six values were computed to calculate the co-efficient of correlation between the scores on each of the six value scales and the scores on anti-minority attitude scale. Results show that a significant positive correlation exists between political and economical values and anti-minority attitude (P